Physical oceanography during RV Sarmiento de Gamboa DESAFIO cruise (January-March 2023) in Northeast Atlantic Ocean - Sarmiento-Lezcano, Airam Nauzet; Couret, María; Díaz-Pérez, Javier; Bernal, Ainhoa; Raya, Vanesa; Pla, Martín; Larrumbide-Zúñiga, Nicolás; Castellón, Arturo; Hernández-León, Santiago (PANGAEA, 2025)
Depth, temperature, and conductivity were recorded during the DESAFIO cruise (from 31st of January to the 2nd of March 2023) using a SeaBird SBE 25plus CTD, the dissolved oxygen with a Seabird-43 sensor both attached to an oceanographic rosette from surface to a maximum depth of 2000 m, and the fluorometer with a Seapoint sensor in the upper 200 m depth. Fluorescence was converted to chlorophyll using samples at discrete depths for calibration. Chlorophyll a (Chl a) was measured ﬁltering 500 ml of seawater through a 25 mm Whatman GF/F ﬁlter and freezing it at -20°C until its analysis in the laboratory. The extraction procedure consisted in placing the ﬁlter in 90% acetone at -20°C in the dark, during 24 h. Pigments were measured on a Turner Design 10A Fluorometer, previously calibrated with pure Chl a (Yentsch and Menzel, 1963, doi:10.1016/0011-7471(63)90358-9) and measured following the acidiﬁcation method by Strickland and Parsons (1972, hdl:10013/epic.46454.d001).
Keywords: Abundance; biological carbon pump; Biomass; electron transport system (ETS); gelatinous zooplankton; Migrant biomass; Pelagic tunicate